A More Drought Resistant Stem Xylem of Southern Highbush Than Rabbiteye Blueberry Is Linked to Its Anatomy - Ya Zhang; Jia-Bao Liu; Xi-Xi Zhang (Agronomy, 2022)
Increasing extreme drought events due to climate change may cause severe damage to blueberry industries, including decreased fruit yield and quality. Previous studies on drought tolerance of blueberries focus mainly on functional changes of leaves, while hydraulic properties of blueberry stems related to drought resistance are poorly reported. Here, both xylem anatomical and functional traits of stems of two southern highbush (SHB) and three rabbiteye blueberry (REB) cultivars were investigated. Compared with REB, SHB showed lower sapwood hydraulic conductivity (KS) and P50 (xylem water potential with 50% embolism in xylem), suggesting that SHB has less conductive but safer xylem than REB. The hydraulic functional differences between two blueberry xylems were highly related to their significant differences in vessel anatomy. Small vessel diameter and total inner pit aperture area per vessel area (APA) limited the hydraulic conductivity of SHB xylem, but high conduit wall reinforcement, wood density, and vessel-grouping index in SHB xylem showed strong mechanical support and safe water transport. Besides, pseudo-tori pit membranes were found in all five cultivars, while the similar thickness of homogenous pit membrane in two blueberry species was not linked to other functional traits, which may be due to its limited measurements. These results reveal a trade-off between the water transport efficiency and safety in the blueberry xylem and clarify the variance of stem drought resistance in different cultivars from a hydraulic perspective. Further studies with such a perspective on other organs of blueberries are required to understand the drought tolerance of a whole plant, which builds a solid foundation for the introduction, cultivation, and management of blueberry industries.